1996
DOI: 10.1016/0014-5793(96)00214-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dystrophin‐syntrophin interaction using the two‐hybrid system in yeast

Abstract: The carboxy-terminal region of dystrophin has previously been shown to interact directly with al syntrophin, a cytoplasmic component of the dystrophin-glycoprotein complex, by in vitro biochemical studies such as overlay assay or immunoprecipitation. Using the two-hybrid system, we have isolated from a human heart cDNA library the entire coding sequence of human ~I syntrophin, therefore confirming for the first time this interaction via an in vivo approach. In addition, we have reduced the interaction domain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…31 The physical interaction between mammalian syntrophin and dystrophin has been demonstrated by a variety of methods, including overlay assay, in vitro binding and immunoprecipitation, and yeast two-hybrid assay. 17,18,34,35 In contrast, despite earlier evidence that C. elegans syntrophin and dystrophin bind to each other in in vitro pulldown experiments, 19 we were not able to show any interaction in the yeast two-hybrid assay, which is considered to be closer to the in vivo situation than in vitro experiments are. The two-hybrid result is in accordance with the absence of a clear syntrophin binding site (as defined by Newey and colleagues 31 ) on the C. elegans dystrophin sequence.…”
Section: Discussioncontrasting
confidence: 81%
“…31 The physical interaction between mammalian syntrophin and dystrophin has been demonstrated by a variety of methods, including overlay assay, in vitro binding and immunoprecipitation, and yeast two-hybrid assay. 17,18,34,35 In contrast, despite earlier evidence that C. elegans syntrophin and dystrophin bind to each other in in vitro pulldown experiments, 19 we were not able to show any interaction in the yeast two-hybrid assay, which is considered to be closer to the in vivo situation than in vitro experiments are. The two-hybrid result is in accordance with the absence of a clear syntrophin binding site (as defined by Newey and colleagues 31 ) on the C. elegans dystrophin sequence.…”
Section: Discussioncontrasting
confidence: 81%
“…Therefore, the mechanical and nonmechanical defects that arise in muscular dystrophy may occur in part from the loss of these proteins. Dystrophin and the syntrophins, the cytoplasmic components of the DGC, can directly interact (Adams et al, 1993;Ahn and Kunkel, 1995;Ahn et al, 1994;Castello et al, 1996;Peters et al, 1997;Suzuki et al, 1994Suzuki et al, , 1995Yang et al, 1995). Syntrophin interacts with a number of other elements including nitric oxide synthase (Hashida-Okumura et al, 1999;Venema et al, 1997), voltage gated sodium channels (Gee et al, 1998;Schultz et al, 1998), stress activated protein kinase-3 (Hasegawa et al, 1999), caveolin via NOS (Venema et al, 1997), calmodulin , and phosphatidylinositol 4,5-bisphosphate (Venema et al, 1997).…”
Section: Membrane-cytoskeletal-extracellular Matrixmentioning
confidence: 99%
“…Previous studies have shown that these domains are sufficient to mediate the physical interaction between the two proteins and that this interaction likely takes place between the first helices (H1) of each protein [6]. The protein region directly upstream of H1 in both dystrophin and dystrobrevin long isoforms is thought to associate with syntrophins [6,7].…”
Section: Introductionmentioning
confidence: 99%